2021
DOI: 10.1002/pat.5470
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of the stress cracking behavior of PBT by acoustic emission

Abstract: Despite being a major cause of failure of polymer products under service, environmental stress cracking (ESC) is still a phenomenon poorly investigated and, as consequence, not fully understood. This article aims to contribute to this field in a study of the stress cracking behavior of polybutylene terephthalate (PBT) exposed to ethanol (a common fluid, used in several daily situations), by means of two types of mechanical tests (tensile and stress relaxation). During mechanical testing the technique of acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…One can also note from Fig. 2 b that the possible degradation induced by injection process does not significantly affect neither the Young's modulus nor the yield stress (NB: consistently with other recent examples illustrating the effect of crystallinity on PBT storage [16] or modulus average molar mass and crystalline ratio on POM yield stress [17] ).…”
Section: Mechanical Testssupporting
confidence: 87%
“…One can also note from Fig. 2 b that the possible degradation induced by injection process does not significantly affect neither the Young's modulus nor the yield stress (NB: consistently with other recent examples illustrating the effect of crystallinity on PBT storage [16] or modulus average molar mass and crystalline ratio on POM yield stress [17] ).…”
Section: Mechanical Testssupporting
confidence: 87%
“…In the subject of degraded polyester morphology determination, 110–145 several analytical techniques have been used by researchers to reveal the elements of the changes. These techniques include microscopy, gel permeation chromatography, X‐ray diffraction, spectroscopy, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Stress‐cracking behavior of PBT exposed to ethanol during tensile and stress relaxation test was examined and internal failure was determined. The tensile properties were dependent on the crosshead speed, ethanol evaporation, and the crystallinity of samples 133 . In a study of crack growth in PLA, in hydrolysis reaction, it is concluded that the crack velocity was insensitive to load but was sensitive to humidity and pH of the medium 134 .…”
Section: Environmental Stress Cracking Of Pet By Aminolysismentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of the ESC behavior under mechanical load can be carried out under static or dynamic load. Mechanical tests of thermoplastics under static loading, either tensile, bending, or creep tests, are widely known in the literature [11][12][13][14][15][16][17][18][19][20]. These investigations were either carried out on specimens previously immersed in the SCA [20] or during in situ wetting [10,17,18].…”
Section: Introductionmentioning
confidence: 99%